Peluang dan Tantangan Pemerintah Daerah dalam Mengimplementasikan Undang-undang No. 1 Tahun 2022 Tentang HKPD (Studi Tentang Reklasifikasi Pajak Daerah di Kabupaten Banyuwangi) - Amalinda Nazili Hanim (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by the enactment of Law Number 1 of 2022 concerning the Financial Relationship between the Central Government and Regional Governments (HKPD), as a reform of previous fiscal policies regulated under Law No. 33 of 2004 and Law No. 28 of 2009. One of the major changes in this law is the reclassification of local taxes aimed at simplifying the taxation system, increasing efficiency, and strengthening Local Own-Source Revenue (PAD). Banyuwangi Regency was selected as the research location due to its consistent and significant increase in regional tax revenue during the 2019–2023 period and its readiness to implement the new fiscal regulations. The aim of this study is to identify and analyze the opportunities and challenges faced by the Banyuwangi Regency Government in implementing the local tax reclassification under Law No. 1 of 2022. This research uses a qualitative descriptive case study approach, with data collected through interviews, documentation, and field observation. The research findings reveal several opportunities, including the potential for increased PAD, digital tax system modernization, and stronger fiscal independence. However, challenges remain, such as adapting to new tax collection systems, limitations in technological infrastructure, human resources, and adjusting to new tax rates. The Banyuwangi Government responded to these challenges by developing the "SI JAKA WANGI" application, updating local regulations through Regional Regulation No. 1 of 2024, and conducting public education and outreach programs. In conclusion, the implementation of Law No. 1 of 2022 offers strategic opportunities to enhance taxation efficiency and fiscal autonomy. Banyuwangi has demonstrated an adaptive response and can serve as a model for other regions in applying effective fiscal reform.
Entry oleh Arif 2026 Januari 27
Keywords: Local Tax Reclassification; Law No. 1 of 2022; Local Revenue; Banyuwangi; Fiscal Reform